Effect of service sub-sector vulnerability due to the COVID-19 pandemic enhanced community quarantine on the cumulative abnormal returns of service firms listed in the Philippine Stock Exchange with disclosure tone as a moderating variable - Maristela, Micah Jaye R. (Animo Repository, 2022)
The ongoing COVID-19 pandemic has, thus far, presented an extensive set of extraordinary implications that are yet to be fully understood and explored. The business sector, especially the service sector, is known to have taken a particularly negative hit due to the nature of its requirement – face-to-face interaction. Thus, this study was conducted in order to understand the impact of the global pandemic on a local-level by investigating the effect of service sub-sector vulnerability due to an Enhanced Community Quarantine (ECQ) on the Cumulative Abnormal Returns (CAR) of service firms listed in the Philippine Stock Exchange (PSE). Furthermore, the disclosure tone used by the firms in their annual reports was also measured and considered as a moderating variable in the study, to further comprehend the significance of management disclosures towards stock market reactions in such events. An event study, textual content analysis and multiple regression analysis were performed in order to derive the conclusion of this study. The results of the study reveal that immediately after the announcement, when controlled with firm-specific characteristics, service sub-sector vulnerability significantly impacted the stock market performance – in that the non-essential sub-sectors were negatively affected to a greater extent, as opposed to the essential sub-sectors. Whereas, disclosure tone exhibits no moderating effect on the relationship between variables.